2009
DOI: 10.1111/j.1468-3083.2009.03323.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence remission spectroscopy of psoriatic lesions and the effect of topical anthralin therapy

Abstract: Vascular perfusion is increased in psoriatic lesions as demonstrated by remission spectroscopy. NADH-fluorescence is reduced in lesional psoriatic skin and in anthralin-induced erythema. FRIS is a suitable tool for objective evaluation of the cutaneous response to antipsoriatic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(18 reference statements)
0
6
0
1
Order By: Relevance
“…It seems reasonable since the proliferation of psoriatic keratinocytes requires consumption of NADH during oxidative phosphorylation and ATP synthesis. In the study of Wollina et al the NADH fluorescence was found to be reduced in psoriatic lesions [15]. In the search for new antipsoriatic agents NAD(+) used topically was found to be as effective as 0.1% anthralin [16].…”
Section: Wykorzystuje Dinukleotyd Nikotynoamidoadeninowymentioning
confidence: 99%
See 1 more Smart Citation
“…It seems reasonable since the proliferation of psoriatic keratinocytes requires consumption of NADH during oxidative phosphorylation and ATP synthesis. In the study of Wollina et al the NADH fluorescence was found to be reduced in psoriatic lesions [15]. In the search for new antipsoriatic agents NAD(+) used topically was found to be as effective as 0.1% anthralin [16].…”
Section: Wykorzystuje Dinukleotyd Nikotynoamidoadeninowymentioning
confidence: 99%
“…Wollina i wsp. wykazali, że fluorescencja NADH zmniejsza się w zmianach łuszczycowych [15]. Przy poszukiwaniu nowych leków przeciwłuszczycowych stwierdzono, że stosowany miejscowo NAD(+) jest równie skuteczny jak 0,1% antralina [16].…”
Section: Wykorzystuje Dinukleotyd Nikotynoamidoadeninowyunclassified
“…On the one hand, one can speculate that increased proliferation and inflammation in a psoriatic lesion result in NADH rapid consumption. Wollina et al revealed that indeed the NADH fluorescence, which reflects NADH amount in the skin, was reduced in psoriatic lesions [15]. Unfortunately, this is the only existing study devoted to determining the NADH level in psoriatic skin in vivo [15].…”
Section: Nicotinamide-adenine Dinucleotide In Psoriasismentioning
confidence: 99%
“…Wollina et al revealed that indeed the NADH fluorescence, which reflects NADH amount in the skin, was reduced in psoriatic lesions [15]. Unfortunately, this is the only existing study devoted to determining the NADH level in psoriatic skin in vivo [15]. An opposite hypothesis links increased cellular metabolism to the increased NADH/NAD + ratio.…”
Section: Nicotinamide-adenine Dinucleotide In Psoriasismentioning
confidence: 99%
“…The average total energy applied was 2.05 J, with 1.13 J in the UVB med range. We used the fluorescence‐remission imaging (FRIS) as described before 7 for non‐invasive objective measurements.…”
Section: Clinical Outcome Lesion a – 307 Nm‐excimer Light; Lesion Bmentioning
confidence: 99%